Supercapacitive performance and CO2 capture capacities of different porous corn stover-derived activated carbons - Gbenebor, Oluwashina Philips; Popoola, Abimbola Patricia Idowu (Center of Biomass & Renewable Energy (CBIORE), 2025)
This work focuses on synthesizing activated carbon (AC) from corn wastes from the same plantation – husk (ACH), stalk (ACS), and cob (ACCo). A two-stage pyrolysis (600 oC) with KOH chemical activation was employed. Structural and morphological results from Fourier Transform Infrared spectroscopy (FTIR) and Scanning Electron Microscope (SEM) show that the temperature, concentration, and ratio of biochar-to-KOH solution employed are effective as relevant functional groups and porous structures are formed. The best porous texture is possessed by ACH as N2 adsorption isotherms result informs that its surface area, pore volume, and size are 904.76 m2/g, 1.00 cm3/g, and 2.09 nm respectively. At 273 K, ACH displays the highest CO2 adsorption capacity of 4.63 mmolg-1 at 0.95 bar while ACS and ACCo possess CO2 capture capacities of 3.5 and 3.19 mmolg-1 respectively. Each synthesized AC electrode displays capacitive performance with pseudo capacitance contributions. Dunn and Trasatti analyses show that the capacity of each electrode is more influenced by diffusive contribution. The best porous structure exhibited by ACH is responsible for its superlative electrochemical performance. At current density of 0.5 A/g, its specific capacitance is 430 F/g; this is followed by ACS (257.5 F/g) and the least specific capacitance of 85 F/g is achieved by ACCo. Electrochemical Impedance Spectroscopy (EIS) and Bode plots affirm that with ACH, the fastest diffusion of electrolyte ions into its surface is maintained.